Tourmaline Reference Materials for the In Situ Analysis of Oxygen and Lithium Isotope Ratio Compositions. Issue 1 (7th November 2020) - Wiedenbeck, Michael; Trumbull, Robert B.; Rosner, Martin; Boyce, Adrian; Fournelle, John H.; Franchi, Ian A.; Halama, Ralf; Harris, Chris; Lacey, Jack H.; Marschall, Horst; Meixner, Anette; Pack, Andreas; et al.
Abstract : Three tourmaline reference materials sourced from the Harvard Mineralogical and Geological Museum (schorl 112566, dravite 108796 and elbaite 98144), which are already widely used for the calibration of in situ boron isotope measurements, are characterised here for their oxygen and lithium isotope compositions. Homogeneity tests by secondary ion mass spectrometry (SIMS) showed that at sub‐nanogram test portion masses, their 18 O/ 16 O and 7 Li/ 6 Li isotope ratios are constant within ± 0.27‰ and ± 2.2‰ (1 s ), respectively. The lithium mass fractions of the three materials vary over three orders of magnitude. SIMS homogeneity tests showed variations in 7 Li/ 28 Si between 8% and 14% (1 s ), which provides a measure of the heterogeneity of the Li contents in these three materials. Here, we provide recommended values for δ 18 O, Δ' 17 O and δ 7 Li for the three Harvard tourmaline reference materials based on results from bulk mineral analyses from multiple, independent laboratories using laser‐ and stepwise fluorination gas mass spectrometry (for O), and solution multi‐collector inductively coupled plasma‐mass spectroscopy (for Li). These bulk data also allow us to assess the degree of inter‐laboratory bias that might be present in such data sets. This work also re‐evaluates the major element chemical composition of the materials by electron probe microanalysis and investigates these presence of a chemical matrix effect on SIMS instrumental mass fractionation with regard to δ 18 O determinations, which was found to be < 1.6‰ between these three materials. The final table presented here provides a summary of the isotope ratio values that we have determined for these three materials. Depending on their starting mass, either 128 or 512 splits have been produced of each material, assuring their availability for many years into the future. Key Points: Three widely available tourmaline reference materials are characterized for δ 7 Li, δ 17 O and δ 18 O, while new EPMA and SIMS measurements refine their major element compositions. SIMS data document homogeneity for these isotope ratios. SIMS matrix effect causes bias of 1.9‰ between elbaite and schorl, whereas silicate glass shows even more severe bias.